2018
DOI: 10.2147/copd.s163659
|View full text |Cite
|
Sign up to set email alerts
|

Comorbidities, mortality, and management of chronic obstructive pulmonary disease patients who required admissions to public hospitals in Hong Kong – computerized data collection and analysis

Abstract: BackgroundCOPD is a common cause for hospital admission. Conventional studies of the epidemiology of COPD involved large patient number and immense resources and were difficult to be repeated. The present study aimed at assessing the utilization of a computerized data management system in the collection and analysis of the epidemiological and clinical data of a large COPD cohort in Hong Kong (HK).Patients and methodsIt was a computerized, multicenter, retrospective review of the characteristics of patients dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…4,5 One possible explanation is that a significant proportion of our patients with pneumonia as their assigned cause of death might have underlying COPD, a risk factor of and one of the most frequent comorbidities with pneumonia, which is a major cause of death among COPD patients. 40 As our mortality analysis was based on a single cause of death per deceased person, this may introduce inaccuracy in death-cause assignment for patients with multi-comorbidity, which is nonetheless more common in schizophrenia patients than the general population. Alternatively, our findings that mortality rates for cancers were not significantly elevated among patient groups are at odds with most, 41 though not all, 42 past studies reporting heightened cancer mortality rate in schizophrenia.…”
Section: Discussionmentioning
confidence: 99%
“…4,5 One possible explanation is that a significant proportion of our patients with pneumonia as their assigned cause of death might have underlying COPD, a risk factor of and one of the most frequent comorbidities with pneumonia, which is a major cause of death among COPD patients. 40 As our mortality analysis was based on a single cause of death per deceased person, this may introduce inaccuracy in death-cause assignment for patients with multi-comorbidity, which is nonetheless more common in schizophrenia patients than the general population. Alternatively, our findings that mortality rates for cancers were not significantly elevated among patient groups are at odds with most, 41 though not all, 42 past studies reporting heightened cancer mortality rate in schizophrenia.…”
Section: Discussionmentioning
confidence: 99%
“…Anonymized patient data could be retrieved and analyzed using the HA Clinical Data Analysis and Reporting System (CDARS) software program. 3–5 Previous published data of 14 public hospitals in HK showed that it is possible to review the health-care utilization of an anonymized COPD patient cohort (N = 9776) in year 2012 using CDARS. 3 The present study aimed to assess the trend of hospital burden of COPD from 2006 to 2014 – including the demographic data, use of health-care resources, mortality and survival.…”
Section: Introductionmentioning
confidence: 99%
“… 3–5 Previous published data of 14 public hospitals in HK showed that it is possible to review the health-care utilization of an anonymized COPD patient cohort (N = 9776) in year 2012 using CDARS. 3 The present study aimed to assess the trend of hospital burden of COPD from 2006 to 2014 – including the demographic data, use of health-care resources, mortality and survival. HK has a population of over 7 million and the present study included the medical departments of all acute public hospitals (N = 15) and chest hospitals (N = 4) in HK.…”
Section: Introductionmentioning
confidence: 99%
“… 20 Inaccurate diagnosis due to lack of a popper lung function test, underutilization of long-acting bronchodilators and lack of an integrative care model were postulated to be the main issues to be tackled. 21 To bridge this service gap, a COPD audit had been conducted across all primary care clinics of HAHK since 1st April 2017 with the purpose to plug these loopholes in COPD management and to enhance the quality of care. This study aimed to review the management of COPD cases from all primary care clinics of HAHK via a two phase clinical audit and to share out the improvement strategies.…”
Section: Introductionmentioning
confidence: 99%